A qualitative photographic analysis of Guardian figures in Chinese temples in Bali: visual rhetoric and cultural hybridity - Dinata, Ramanda Dimas Surya; Hendrawan, Freddy; Setyawan, Agus Budi; Prameswari, Gusti Ayu Ratih (Institut Seni Indonesia Surakarta, 2025)
This study investigates how the guardian figures in Chinese temples across Bali visually represent cultural hybridity between Chinese religious traditions and Balinese symbolic aesthetics. Using a descriptive-interpretive qualitative approach based on the idea of visual rhetoric, this study examines seven temples across Balinese regencies. Photographic documentation and ethnographic interviews with temple representatives and craftsmen were conducted to collect data. In this sense, photography is a documentation tool, yet also a visual analysis method, providing a deeper interpretation of cultural negotiation. This study shows that while the guardian figures within the Chinese temples in Bali retain core Chinese iconographic elements, such as mythological animals and heroic deities, they also adopt Balinese traditional ornaments. Due to influenced by the both Chinese and Balinese heritage of the Chinese-Balinese community, these visual adaptations demonstrate a conscious integration of Balinese cultural identity within Chinese sacred forms. In this sense, guardian figures play a significant role as visual intermediaries within sacred spaces, representing both protective symbolism and the spatial hierarchy of the temple’s design. Ultimately, this study contributes to the understanding of transcultural religious design and provides insights into the role of visual culture as a medium of spiritual expression and the construction of hybrid identity within a multicultural urban environment.